Physiological and biochemical changes induced by drought stress during the stem elongation and anthesis stages in the Triticum genus - Pantha, Sumitra; Kilian, Benjamin; Özkan, Hakan; Zeibig, Frederike; Frei, Michael; Justus Liebig University Giessen (My University, 2024)
Drought stress negatively influences the growth, development, and grain yield of wheat by disrupting its morphological, physiological, and biochemical processes. This study examined the effects of drought stress during the stem elongation and anthesis developmental stages of species within the Triticum genus along with their drought adaptation mechanisms under fully watered and drought conditions. We tested the following two hypotheses: (1) drought tolerance mechanisms for osmotic and stomatal regulation that lead to oxidative stress are correlated between the stem elongation and anthesis stages and affect grain yield loss, and (2) compared with modern cultivars, wild wheat cultivars exhibit greater drought tolerance. To test these hypotheses, a greenhouse pot experiment was conducted using 17 genotypes of wild wheat relatives and landraces, with modern cultivars included for comparison. Drought stress was induced during the stem elongation and anthesis stages until the average soil moisture was approximately 15 % and 18 %, respectively, of the pot’s water holding capacity. The soil moisture was maintained at 80–90 % for the fully watered treatment. An examination of physiological and biochemical traits revealed that drought significantly reduced stomatal conductance (gsw) and relative water content (RWC) during both developmental stages. However, significant increases occurred in the malondialdehyde (MDA) content during both stages and in the proline content during the anthesis stage. Drought stress significantly decreased the number of days to heading and anthesis, indicating that drought escape occurs under severe drought stress. Furthermore, drought significantly decreased morphological and yield-related traits, with the greatest reduction (51 %) occurring in grain yield. Weakly significant positive associations of biochemical and some physiological traits between the stem elongation and anthesis stages partially confirmed our first hypothesis, whereas our results relating to the second hypothesis were inconclusive. We observed genotype-dependent responses to drought stress during both stages for various measured traits. No associations of RWC, proline, or MDA with grain yield were found. However, stomatal conductance was negatively correlated with grain yield under drought stress at the anthesis stage. Certain wild wheat genotypes and landraces exhibited drought avoidance, escape, and tolerance mechanisms, which positively contributed to grain yield. We identified T. monococcum subsp. sinskajae, T. boeoticum and T. dicoccoides as the most drought-tolerant genotypes. The findings of this study provide important insight for understanding the drought adaptation traits and their use in wheat breeding programs.
Keywords: ddc:630